Psoriatic arthritis epidemiology, comorbid disease profiles and risk factors: Results from a claims database analysis - Rech, Jürgen; Sticherling, Michael; Stoessel, Daniel; Biermann, Mona H.C.; Häberle, Benjamin M.; Reinhardt, Maximilian (Rheumatology Advances in Practice, 2020)
Objective. Psoriasis is a systemic inflammatory disease often accompanied by comorbidities, including metabolic syndrome, cardiovascular diseases and depression. Up to 41% of psoriasis patients develop psoriatic arthritis (PsA), making it one of the most relevant manifestations. A large health claims data set was analysed to determine the rate of PsA development in psoriasis patients. Furthermore, comorbid disease profiles of psoriasis patients with or without PsA were compared, and potential risk factors for the development of PsA were identified. Methods. This was a non-interventional, retrospective analysis of anonymized insurance health claims data using a subset of the Institute of Applied Health Research Berlin (InGef) database. The primary outcome was the prevalence and incidence of diagnosed PsA among psoriasis patients in Germany. Risk factors for the development of PsA in psoriasis patients were determined by conditional logistic regression analysis. Results. The cumulative percentage of patients with existing psoriasis developing concomitant PsA over 4 years was 3.44%, with a mean time to diagnosis of PsA of 1.5 years. Psoriasis patients diagnosed with acute rheumatism (odds ratio: 2.93, 95% CI=1.76, 4.86; P<0.001) or pain in unspecific joints (odds ratio: 1.74, 95% CI=1.01, 2.99; P=0.047) showed an increased risk for development of PsA later on. Interestingly, fewer than half of the patients with concomitant PsA consulted a rheumatologist. Conclusions. Unspecific arthritic symptoms are likely to precede PsA diagnoses and can develop soon after onset of psoriasis, with accumulating risk over time. There is a high unmet need for early rheumatological assessment of psoriasis patients.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Comorbid disease; Epidemiology; Incidence; Insurance health claims data; PsA; Psoriasis; Risk factors